Kesadaran Membayar Pajak Memediasi Hubungan Pengetahuan Perpajakan Terhadap Kemauan Membayar Pajak - Popy Purnamasari; Rachmawati Meita Oktaviani (Jurnal Akuntansi dan Pajak, 2020)
This study aims to examine and analyze the influence of knowladge taxation on the willingness to pay taxes with the awareness of paying taxes as an intervening variabel. The population in this study is the UMKM taxpayer who has an NPWP and is registered with the Semarang Coperation and UMKM Office. Thi study used a nonprobabilitas sampling technique with purpopsive sampling method of 100 respondents. Data analysis of this study using multiple linear analysis and path analysis. The results of the study indicate that the variabel knowledge of tax have a significant positive effect the awareness of paying taxes. Awareness of paying taxes have a significant positive effect the willingness to pay taxes. Knowledge of tax have a significant positive effect on the willingness of pay taxes.